One-stage correction of multiple brachymetatarsia and hallux valgus with calcaneal autograft - Rocha, Felipe Almeida; Mansur, Henrique; Meira, Rubens Theodoro; Gusmão, Lucio; Gonçalves, Cesar Barbosa; de Castro Junior, Isnar Moreira (Scientific Journal of the Foot & Ankle, 2018)
Brachymetatarsia is the shortening of the metatarsus caused by congenital premature closure of the metatarsal physis. In general, the patient presents a shortened and dorsally situated toe causing metatarsalgia in addition to aesthetic effects. The aim of surgery is to improve the symptoms and aesthetics through bone elongation and rebalancing of the metatarsal formula. This elongation may be performed through gradual distraction with an external fixator or a single procedure with a bone graft. We report a case of bilateral brachymetatarsia of the 3rd and 4th metatarsals associated with hallux valgus and deformities in the 2nd toe, in which surgery was performed on the right foot with a calcaneal autograft. Level of Evidence V; Therapeutic Studies; Expert Opinion.